CD38 affects the biological behavior and energy metabolism of nasopharyngeal carcinoma cells - Ge, Yanshan (Int J Oncol, 2018)
Nasopharyngeal carcinoma (NPC) is the most common malignant tumor type in Southern China and South-East Asia. Cluster of differentiation (CD)38 is highly expressed in the human immune system and participates in the activation of T, natural killer and plasma cells mediated by CD2 and CD3 through synergistic action. CD38 is a type II transmembrane glycoprotein, which was observed to mediate diverse activities, including signal transduction, cell adhesion and cyclic ADP-ribose synthesis. However, the significance of CD38 in NPC biological behavior and cellular energy metabolism has not been examined. In order to elucidate the effect of CD38 on the biological behavior of NPC cells, stable CD38-overexpressed NPC cell lines were established. It was demonstrated that CD38 promoted NPC cell proliferation with Cell Counting Kit-8 and colony formation assays. It was also indicated that CD38 inhibited cell senescence, and promoted cell metastasis. Furthermore, it was determined that CD38 promoted the conversion of cells to the S phase and decreased the content of reactive oxygen species and Ca(2+). Additionally, cell metabolism assays demonstrated that CD38 increased the concentration of ATP, lactic acid, cyclic adenosine monophosphate and human ADP/acrp30 concentration in NPC cells. To investigate the possible mechanism, bioinformatics analysis and mass spectrometry technology was used to determine the most notably changing molecule and signaling pathways, and it was determined and verified that CD38 regulated the metabolic-associated signaling pathways associated with tumor protein 53, hypoxia inducible factor-1α and sirtuin 1. The present results indicated that CD38 may serve a carcinogenic role in NPC by regulating metabolic-associated signaling pathways.